Pengaruh Sistem Pembayaran QRIS Terhadap Kepuasan Pelanggan Di Kantin Universitas Dinamika Bangsa Jambi - Adilah, Alifah; Nofril, Nabila Cantika; Devi, Tiara Synta; Wafi, Akhdan; Sabela, Istawa Dina; Kadar, Melani; Yossinomita, Yossinomita (LPPM STIKOM Dinamika Bangsa, 2026)
This study analyzes the impact of QRIS usage on customer satisfaction at the Universitas Dinamika Bangsa (UNAMA) cafeteria. Utilizing a quantitative approach, this research examines the relationship between ease of use and speed (X1), security and comfort (X2), as well as features and support (X3) on customer satisfaction (Y) through regression analysis. The findings indicate that ease of use and speed (X1) do not significantly affect customer satisfaction (t = 0.667; sig = 0.500), suggesting that students do not prioritize these aspects in their transactions. In contrast, security and comfort (X2) have a significant influence (t = 6.284; sig < 0.001), highlighting that students value these factors more when making transactions. Features and support (X3) also show a significant impact (t = 2.545; sig = 0.012), emphasizing the importance of additional features and technical support in enhancing user satisfaction. Overall, the three variables explain 61% of customer satisfaction, while the remaining 39% is influenced by other factors. This study confirms that while QRIS improves transaction efficiency, ease of use and speed do not sufficiently influence customer satisfaction. This may be due to user habits or their expectations of digital payment systems. Further evaluation is necessary to enhance the transaction experience at the Universitas Dinamika Bangsa Jambi cafeteria.